SOCIAL MEDIA IMPACT ON UITM SEREMBAN 3 STUDENTS’ ENVIRONMENTAL AWARENESS - Farah Adilla Ab Rahman; Nurul Anis Athirah Nor Aspari; Nur Izzatie Mohd Shair; Jeniwaty Mohd Jody (Journal of Islamic, Social, Economics and Development, 2023)
The aim of this study was to investigate the influence of social media on the knowledge, attitude, and practices of environmental awareness among Bachelor of Environmental Administration students at UiTM Seremban 3, as well as to identify the relationship between students' awareness towards the usage of social media in spreading environmental awareness. Quantitative research methods and convenience sampling were employed, with 168 participants completing a questionnaire over the course of two semesters. Data were analyzed using SPSS software. The findings indicated that most respondents had a high level of knowledge regarding environmental awareness, but there was a discrepancy between knowledge and practice. While knowledge and attitude were found to have a positive correlation with environmental awareness, practice did not. Therefore, it is crucial for all parties, including the university, to collaborate in promoting environmental awareness, which should be seen as more than just knowledge, but also as a set of attitudes and practices that can be applied in daily life.